An Overview of Cloud Computing (International Journal of Innovative Research in Computer Science & Technology, 2021)
Cloud computing is a model for giving on demand internet access to common pools of configurable  computer assets (e.g., networks, computers, memory, apps,  and applications) that might be instantly given and released  with minimum administrative effort or participation from  service providers. Clouds computer has risen to prominence  as a key technical trend, with several experts anticipating that  it would transform IT processes and the IT sector. Users may  download software, storage, and software frameworks  through the Internet using a variety of devices, including  PCs, notebooks, cell phones, and PDAs, thanks to cloud  services supplied by clouds computer companies. This article  provides an introduction of clouds computer technologies  installation techniques, classifications, and characteristics.  The term "cloud computing" refers to a type of computer and  communications technology that provides on-demand  services. There is no precise meaning for the word Cloud  Computing.
Keywords: Cloud Computing; Infrastructure; Information Technology; Platform; Software